Sialolipoma: An interesting and rare tumor of the submandibular gland - Satvinder Singh Bakshi; Anandraj K Vaithy (Apollo Medicine, 2019)
Salivary glands containing coexisting lipomatous lesions are rare and have only been identified recently as a distinct entity; one of these lesions is a sialolipoma. The characteristic feature of these tumors is benign proliferation of mature adipose tissue along with normal salivary gland features. We describe a case of a slowly enlarging mass in the submandibular region of a 45-year-old male which on excision was reported as sialolipoma.